1942
DOI: 10.1002/zaac.19422490302
|View full text |Cite
|
Sign up to set email alerts
|

Über eine neue Reaktion des Chlordioxyds. Die Bildung einer Verbindung der Formel ClO2F

Abstract: 1. Aus gasförmigem Chlordioxyd und Fluor läßt sich unter ge‐eigneten Bedingungen, z. B. Chlordioxyd‐Druckenivon etwa 25 mm oder darunter, Fluordrucken von etwa 50 mm und Zusatz mehrerer hundert Millimeter inerten Gases bei einem Gesamtdruck von 1 Atm. und Temperaturen um 0°C, eine Verbindung von der Zusammensetzung ClO2F darstellen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1953
1953
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…Chlorosyl fluoride, ClOF, has a short lifetime and disproportionates into ClF and ClO 2 F [1–4] . The latter, called chlorine dioxide fluoride or chloryl fluoride, is one of the known stable oxyfluorides of chlorine [5–8] . The other ones are chlorine oxide trifluoride ClOF 3 , perchloryl fluoride ClO 3 F, and chlorine dioxide trifluoride ClO 2 F 3 [9–14] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chlorosyl fluoride, ClOF, has a short lifetime and disproportionates into ClF and ClO 2 F [1–4] . The latter, called chlorine dioxide fluoride or chloryl fluoride, is one of the known stable oxyfluorides of chlorine [5–8] . The other ones are chlorine oxide trifluoride ClOF 3 , perchloryl fluoride ClO 3 F, and chlorine dioxide trifluoride ClO 2 F 3 [9–14] .…”
Section: Introductionmentioning
confidence: 99%
“…ClO 2 F can be synthesized by different methods, the most important ones being the fluorination of ClO 2 (Equation (1)) or of chlorates, A [ClO 3 ] ( A =Na, K) (Equation (2) and Equation ) [5,8,16–19] true24ptClO2+normalF224ptClO2normalF true64ptnormalK[ClO3]+104ptBrF364ptnormalK[BrF4]+24ptBr2+34ptnormalO2+64ptClO2normalF true6A[]ClO3+44ptClF364ptAnormalF+24ptCl2+34ptnormalO2+64ptClO2normalFA=Na,K …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chlorine oxide trifluoride, ClOF 3 , [1–3] is one of the currently known four stable chlorine oxyfluorides with the other three being ClO 2 F, ClO 3 F and ClO 2 F 3 [4–9] . Chlorosyl fluoride, ClOF, is unstable towards disproportionation into ClF and ClO 2 F, and is formed as an intermediate during the hydrolysis of ClF 3 [10–14] .…”
Section: Introductionmentioning
confidence: 99%
“…Schmitz and Shumacher (44) showed that the controlled reaction of fluorine and chlorine dioxide results in the formation of a compound FCIO z with a covalently bonded fluorine atom. A similar reaction was expected to occur with tetrafluorohydrazine.…”
Section: Resultsmentioning
confidence: 99%